Correction: Svobodova et al. N6-Adenosine Methylation in RNA and a Reduced m3G/TMG Level in Non-Coding RNAs Appear at Microirradiation-Induced DNA Lesions. Cells 2020, 9, 360 - Kovaříková, Alena Svobodová; Stixová, Lenka; Kovařík, Aleš; Komůrková, Denisa; Legartová, Soňa; Fagherazzi, Paolo; Bártová, Eva (Cells, 2024)
The affiliation number 1, "Institute of Biophysics of the Czech Academy of Sciences, Královopolská 135, 612 65 Brno, Czech Republic" changed its zip code to 612 00 [...].